A Prospective Observational Study of Candidemia: Epidemiology, Therapy, and Influences on Mortality in Hospitalized Adult and Pediatric Patients - Pappas, Peter G.; Rex, John H.; Lee, Jeannette; Hamill, Richard J.; Larsen, Robert A.; Powderly, William; Kauffman, Carol A.; Hyslop, Newton; Mangino, Julie E.; Chapman, Stanley; Horowitz, Harold W.; Edwards, John E.; et al. (Clinical infectious diseases, 2003)
We conducted a prospective, multicenter observational study of adults (n = 1447) and children (n = 144) with candidemia at tertiary care centers in the United States in parallel with a candidemia treatment trial that included nonneutropenic adults. Candida albicans was the most common bloodstream isolate recovered from adults and children (45% vs. 49%) and was associated with high mortality (47% among adults vs. 29% among children). Three-month survival was better among children than among adults (76% vs. 54%; P < .001). Most children received amphotericin B as initial therapy, whereas most adults received fluconazole. In adults, Candida parapsilosis fungemia was associated with lower mortality than was non-parapsilosis candidemia (24% vs. 46%; P < .001). Mortality was similar among subjects with Candida glabrata or non-glabrata candidemia; mortality was also similar among subjects with C. glabrata candidemia who received fluconazole rather than other antifungal therapy. Subjects in the observational cohort had higher Acute Physiology and Chronic Health Evaluation II scores than did participants in the clinical trial (18.6 vs. 16.1), which suggests that the former subjects are more often excluded from therapeutic trials.